Impact of safflower oil derived conjugated linoleic acid supplementation on fatty acids profile, lipolysis and sensory properties of cheddar cheese - Khan, Awais; Nadeem, Muhammad; Ahmad, Muhammad Haseeb; Tayyab, Muhammad; Rahim, Muhammad Abdul; Awuchi, Chinaza Godswill (International Journal of Food Properties, 2022)
Nutritionists recommend to consume 3 g Conjugated linoleic acid (CLA) to prevent cancers, cardiovascular diseases, diabetes, obesity and other lifestyle-related disorders. To fulfill the daily requirements of CLA, large proportions of dairy and meat products have to be included in the dietary plan that may have negative impacts such as excessive intake of fat, cholesterol, and lactose. Current investigation was aimed to determine the effect of safflower oil derived CLA on fatty acids composition, lipolysis and sensory properties of cheddar cheese. Safflower oil-derived conjugated linoleic acid (CLA) was added to cheddar cheese at four levels i.e. 1%, 2%, 3% and 4% concentrations (T1, T2, T3 & T4), cheese without CLA supplement was used as control, vacuum packaged samples were ripened at 6–8°C for 90 days. Analysis of CLA supplement revealed that concentrations of ∆9c,11 t-18:2, ∆10 t,12c-18:2, ∆9c,11c-18:2, ∆9 t, 11c-18:2 were 52.16, 44.37, 0.27 and 0.55 mg/100 g. In control, concentrations of ∆9c,11 t-18:2 and ∆10 t,12c-18:2 was 0.24% and 0.07% with a total CLA content of 0.31%. In T3, concentrations of ∆9c,11 t-18:2, ∆10 t,12c-18:2, ∆9c,11c-18:2 and ∆9 t, 11c-18:2 were 1.12, 3.82, 1.63, 2.77 (total CLA 8.34mg100g). In T4, concentrations of ∆9c,11 t-18:2, ∆10 t,12c-18:2, ∆9c,11c-18:2 and ∆9 t, 11c-18:2, were 1.47, 3.50, 3.25 and 3.44% (total CLA 11.67 mg/100 g). Supplementation of cheddar cheese at all four levels significantly increased the concentrations of lactic acid, citric acid, propionic and acetic acids. After 90 days of ripening, free fatty acids in control, T1, T2, T3 and T4 were 0.14, 0.19, 0.23, 0.29 and 0.37% with no difference in composition and sensory properties. These results suggested that CLA content of cheddar cheese can be successfully increased with safflower oil-derived CLA supplement.
Keywords: Sensory properties; CLA; Cheddar cheese; Lipolysis